Highly efficient encapsulation of curcumin into and pH-controlled drug release from poly(ε-caprolactone) nanoparticles stabilized with a novel amphiphilic hyperbranched polyglycerol - N. Zs. Nagy; Z. Varga; J. Mihaly; Gy. Kasza; B. Ivan; E. Kiss (eXPRESS Polymer Letters)
The hardly water-soluble curcumin with low bioavailability was successfully encapsulated into biodegradable polymeric particles by nanoprecipitation. By using the more hydrophobic poly(ε-caprolactone) (PCL) instead of poly(lactic-co-glycolic acid) 50:50 (PLGA) significantly increased drug load was achieved. The stronger interaction between curcumin and PCL than PLGA was supported by Fourier-transform infrared spectroscopy (FTIR) measurements. As efficient colloid stabilizer, a novel amphiphilic polymer, hyperbranched polyglycerol with one long alkyl chain (C18-HbPG) was used which has better membrane affinity than the widely used Pluronics, and it enables further functionalization of the drug carrier as well. A Box-Behnken experimental design was applied to prepare and optimize the properties of curcumin loaded PCL nanoparticles (NPs) varying the initial drug load, composition of the organic phase and volume ratio of aqueous and organic phases. The volume of the organic phase was found to be the most relevant parameter for encapsulation, and it can be used to control the size and drug content of the NPs. The curcumin load of 10 w/w% of the NPs with diameter below 120 nm was observed in the optimal system. Cumulative controlled release of curcumin with strong pH-dependence into simulated gastric fluids with up to ~80% is found after 8–12 hours.